Noah Cleveland Davenport and Clara Ellen Tarte Davenport papers - Davenport, Noah Cleveland, 1885-1976.; Davenport, Clara Ellen Tarte, 1885-1974.
Diary titled, Unalaska days, kept by Noah and Clara Davenport describing their voyage from Seattle, Wash., to the village of Unalaska, Alaska; work as teachers in Unalaska and Noah Davenport's service as U.S. Commissioner; social life and customs of the Aleuts of Unalaska; religious events in the Russian Orthodox Greek Catholic Church and the Jesse Lee Home, a Methodist Episcopal mission and home for Aleut orphans; and the Davenport's return voyage by way of California to their home in Washington. Of special interest are the entries describing the arrival and departure of ships from Unalaska Island and the capture and trials of Japanese seal poachers and use of these prisoners for labor. Diary includes photographs and a detailed record of Davenport's income and expenditures. Includes a typewritten transcript of the diary, genealogical data for the Davenport and Tarte families, reports, maps, and information concerning individuals, ships, and places discussed in the diary.
Microfilm (no. 21,146) and photocopy of Unalaska Days: A Diary available.
Microfilm and photocopy produced from originals in the Manuscript Division.
Educator.
Collection material in English.
Keywords: Jesse Lee Home (Seward, Alaska); Methodist Episcopal Church -- Missions -- Alaska; Russian Orthodox Greek Catholic Church of America; Aleuts; Education -- Alaska; Orphanages -- Alaska; Prisoners, Foreign -- Alaska; Sealing -- Bering Sea; Ships -- Alaska; United States commissioners; Voyages and travels; Alaska -- Description and travel; Alaska -- History -- 1867-1959.; California -- Description and travel; Pacific Coast (North America) -- Description and travel; Unalaska (Alaska) -- Description and travel; Unalaska (Alaska) -- History; Unalaska (Alaska) -- Social life and customs; Unalaska (Alaska) -- Religious life and customs; Washington (State) -- Description and travel; Educators